Effectiveness of water immersion on postmatch recovery in elite professional footballers - Elias, G. P.; Wyckelsma, V. L.; Varley, M. C.; McKenna, M. J.; Aughey, R. J. (International Journal of Sports Physiology and Performance, 2013)
Purpose: The efficacy of a single exposure to 14 min of contrast water therapy (CWT) or cold-water immersion (COLD) on recovery postmatch in elite professional footballers was investigated. Method: Twenty-four elite footballers participated in a match followed by 1 of 3 recovery interventions. Recovery was monitored for 48 h postmatch. Repeat-sprint ability (6 × 20-m), static and countermovement jump performance, perceived soreness, and fatigue were measured prematch and immediately, 24 h, and 48 h after the match. Soreness and fatigue were also measured 1 h postmatch. Postmatch, players were randomly assigned to complete passive recovery (PAS; n = 8), COLD (n = 8), or CWT (n = 8). Results: Immediately postmatch, all groups exhibited similar psychometric and performance decrements, which persisted for 48 h only in the PAS group. Repeat-sprinting performance remained slower at 24 and 48 h for PAS (3.9% and 2.0%) and CWT (1.6% and 0.9%) but was restored by COLD (0.2% and 0.0%). Soreness after 48 h was most effectively attenuated by COLD (ES 0.59 ± 0.10) but remained elevated for CWT (ES 2.39 ± 0.29) and PAS (ES 4.01 ± 0.97). Similarly, COLD more successfully reduced fatigue after 48 h (ES 1.02 ± 0.72) than did CWT (ES 1.22 ± 0.38) and PAS (ES 1.91 ± 0.67). Declines in static and countermovement jump were ameliorated best by COLD. Conclusions: An elite professional football match results in prolonged physical and psychometric deficits for 48 h. COLD was more successful at restoring physical performance and psychometric measures than CWT, with PAS being the poorest.